Graphitized porous carbon nanofibers prepared by electrospinning as anode materials for lithium ion batteries. Issue 86 (1st September 2016) - Zhu, Shoupu; Sun, Jing; Wu, Tian; Su, Xun; Su, Haiming; Qu, Shanshan; Xie, Yongjuan; Chen, Ming; Diao, Guowang
Abstract : Graphitized porous carbon nanofibers were prepared by electrospinning and subsequent calcining, exhibiting high capacity and good cycling stability. Abstract : Graphitized porous carbon nanofibers (GPCNFs) were prepared by electrospinning and a subsequent continuous unique three-part calcining process: pre-oxidation at 250 °C in air for 2 h, graphitization at 1000 °C in Ar for 2 h and pore-forming at 400 °C in air. The physical properties of carbon nanofibers (CNFs) were characterized by X-ray diffraction, thermogravimetric analysis, scanning electron microscopy, transmission electron microscopy, high-resolution transmission electron microscopy, Raman spectroscopy, four-probe measurements and the Brunauer–Emmett–Teller method. The electrochemical properties were observed by cyclic voltammetry and a charge–discharge test of coin-type cells versus metallic lithium. The results showed GPCNFs exhibited good capacity retention and higher capacities than graphitized carbon nanofibers (GCNFs). The capacity of GPCNFs increased with the extension of calcining time at 400 °C from 3 to 18 h. While calcining for 18 h the capacity of GPCNFs achieved 473.5 mA h g −1 after 100 cycles at 0.5 A g −1 . The excellent electrochemical properties of the GPCNFs could be attributed to the small diameter, large specific surface area, little pores and oxygen and nitrogen functional groups, which could promote transmission of lithium ions, provide more space for lithium storage and obtain a high capacity and good cycling stability.